2006
DOI: 10.1111/j.1461-9563.2006.00299.x
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of re‐randomization methods in bark beetle (Scolytidae) trapping bioassays

Abstract: 1 Numerous studies have explored the role of semiochemicals in the behaviour of bark beetles (Scolytidae). 2 Multiple-funnel traps are often used to elucidate these behavioural responses.Sufficient sample sizes are obtained by using large numbers of traps to which treatments are randomly assigned once, or by frequent collection of trap catches and subsequent re-randomization of treatments. 3 Recently, there has been some debate about the potential for trap contamination to occur when semiochemical treatments (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 18 publications
0
8
0
1
Order By: Relevance
“…Although the ternary blend described earlier yielded highest catches and a very large positive effect size ( d unbiased = 1.20) comparable to those in the previous trials, the good results of treatment Id + Ie could not be confirmed. Although one of the experimental blocks was removed because of obvious internal exposure heterogeneity, there was a high chance that randomization procedures did not minimize positional effects, as experimental units were not equally represented (Fettig et al. 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the ternary blend described earlier yielded highest catches and a very large positive effect size ( d unbiased = 1.20) comparable to those in the previous trials, the good results of treatment Id + Ie could not be confirmed. Although one of the experimental blocks was removed because of obvious internal exposure heterogeneity, there was a high chance that randomization procedures did not minimize positional effects, as experimental units were not equally represented (Fettig et al. 2006).…”
Section: Discussionmentioning
confidence: 99%
“…A total of five treatments were thus evaluated within a complete randomized block design. Besides the initial random position assignment, re-randomization of treatment allocation to experimental units within experimental blocks was undertaken on 31 May and 10 August (Fettig et al 2006). Baits were replaced after 6 weeks, well before to the expected duration (SEDQ LLC, Barcelona, Spain).…”
Section: Trapping Bioassaymentioning
confidence: 99%
“…Bark beetle semiochemicals have been classified as either synergists or inhibitors typically with "attractant-challenge"-type experiments in which a bait of undetermined activity is attached to a randomly-selected, attractant-baited trap, and catch is compared to a simultaneously-operated, attractantonly control trap (Reeve and Strom 2004;Fettig et al 2006). If catch in the challenged trap is significantly lower than the control, the test bait is concluded to be inhibitory; if catch is significantly higher than the control, the test bait is concluded to be a synergist or attraction enhancer (Payne et al 1978a;Bedard et al 1980;Bakke 1981;Pureswaran and Borden 2004;Sullivan 2005).…”
Section: Discussionmentioning
confidence: 99%
“…In studies used to identify pheromone synergists and inhibitors for bark beetles (Coleoptera: Scolytidae), candidate behavioral chemicals are typically released from the same location as an attractant, and the ability of the compounds to modify insect flight to the attractant is then measured, usually with a trap (Reeve and Strom 2004;Fettig et al 2006). However, in natural bark beetle attacks, release points of pheromones (i.e., the individual beetle gallery entrances) are dispersed in space and time.…”
Section: Introductionmentioning
confidence: 99%
“…All experiments were conducted using similar protocols and a completely randomized design (Fettig et al 2006b). Sixteen-unit multiple funnel traps (Lindgren 1983) were deployed along forest roads.…”
Section: Methodsmentioning
confidence: 99%